2013
DOI: 10.4062/biomolther.2012.088
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Survivin by Nemadipine-A Sensitizes Cancer Cells to TRAIL-Induced Apoptosis

Abstract: The tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor family of cytokines. TRAIL selectively induces apoptotic cell death in various tumors and cancer cells, but it has little or no toxicity in normal cells. Agonism of TRAIL receptors has been considered to be a valuable cancer-therapeutic strategy. However, more than 85% of primary tumors are resistant to TRAIL, emphasizing the importance of investigating how to overcome TRAIL resistance. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Consistently, it was also found that nemadipine-A potentiates TRAILinduced apoptosis by reducing survivin expression in lung cancer cells. Although, the precise mechanisms are not clear, it was recently reported that survivin expression could be up-regulated by cellular calcium level [53] . Moreover, derivatives of the natural alkaloid camptothecin have the ability to provoke proteasomal degradation of survivin in cells with defective p53 function and elevated XAFI (another tumor suppressor) expression [54] .…”
Section: Chemotherapy and Survivinmentioning
confidence: 99%
“…Consistently, it was also found that nemadipine-A potentiates TRAILinduced apoptosis by reducing survivin expression in lung cancer cells. Although, the precise mechanisms are not clear, it was recently reported that survivin expression could be up-regulated by cellular calcium level [53] . Moreover, derivatives of the natural alkaloid camptothecin have the ability to provoke proteasomal degradation of survivin in cells with defective p53 function and elevated XAFI (another tumor suppressor) expression [54] .…”
Section: Chemotherapy and Survivinmentioning
confidence: 99%
“…Thus, survivin protein represents an attractive target in cancer therapy. Indeed, downregulation of survivin by chemotherapeutic agents or RNA interference resulted in caspase activation and increased apoptotic cell death in cancer cells (27, 28). In addition to its role in promoting cell survival through inhibition of apoptosis, it has been postulated that survivin also plays a role as mitotic inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Survivin is expressed in various types of cancer, including YM155 sensitizes HeLa cells to TRAIL-mediated apoptosis via cFLIP and survivin downregulation breast cancer (16), cervical cancer (17), non-small cell lung cancer (18) and osteosarcoma (19). Its upregulation is associated with survival and resistance to TRAIL-based therapy (20,21).…”
Section: Introductionmentioning
confidence: 99%